2018
DOI: 10.1002/srin.201800121
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Data Driven Modeling and Multi Objective Optimization of Noisy Data Set in Blast Furnace Iron Making Process

Abstract: Data driven models are constructed for the tuyere cooling heat loss, total blast furnace gas flow, tuyere velocity, productivity, and coke rate for an operational blast furnace of an integrated steel plant by using evolutionary computation methods like bi objective genetic programming (BioGP) and evolutionary neural network (EvoNN), which serve as the objectives for their optimization. The models are used to compute the Pareto tradeoff between these conflicting objectives with the help of predator prey genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The normalized data is examined using box plots to check the distribution and identify possible outliers. Box plots can be used to display statistics such as median, quartiles, minimum and maximum values of the data, as well as outliers of the data 30) . In this study, box plots were used to analyze the data collected.…”
Section: Feature Selectionmentioning
confidence: 99%
“…The normalized data is examined using box plots to check the distribution and identify possible outliers. Box plots can be used to display statistics such as median, quartiles, minimum and maximum values of the data, as well as outliers of the data 30) . In this study, box plots were used to analyze the data collected.…”
Section: Feature Selectionmentioning
confidence: 99%
“…This is much more streamlined than tuning the models manually but naturally leaves room to quantify even the best compromising model. This can be accomplished, for example, by using an information-based criterion [89,90]. This approach was also implemented later by Pettersson et al [91,92], and the final selected networks were shown, in each case, to perform better than an analytical model of the system.…”
Section: Applicationsmentioning
confidence: 99%
“…This approach was also implemented later by Pettersson et al [91,92], and the final selected networks were shown, in each case, to perform better than an analytical model of the system. As noted by Mahanta and Chakraborti in their application of an EvoNN to blast-furnace operating data [89], there may be other constraints, for example, financial or practical, which can guide selection of a single optimal solution for a particular scenario.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this is rarely available in the case of batch processes like hot metal desulfurization. Similar to Saxén et al, Mahanta et al applied an evolutionary neural network and bi‐objective genetic algorithm in the optimization of model structure for predicting several operational parameters in a blast furnace. They presented a pareto‐optimal set of input variables, i.e.…”
Section: Introductionmentioning
confidence: 99%